Ampas Tahu Fermentasi Sebagai Bahan Pakan Ayam Pedaging - Luthfi D Mahfudz (Caraka Tani: Journal of Sustainable Agriculture, 2006)
Research about the use of tofu by product as feeds in broiler have been done used 60 broiler, Arbor Acres strain 1 week age which 120,08 ± 15,58 g of body weight. Tofu by product as one of component in feeds, fermented by yeast contain Rhyzopus Oligosporus and R. Oryzae. Feeds compiled with isoprotein and iso energy. In first period, protein content in feeds are 22% and 2.900 kkal/kg of metabolic energy, while in last period protein content are 20% and 3.000 kkal/kg of metabolic energy. Treatment in this research defined as the level of fermented tofu by product in feeds. The treatment are T0, T1, T2 and T3 that containing 0%, 10%, 15% and 20% of fermented tofu by product. Parameter observed are feeds consumption, daily gain, feed coversion ratio, final weight and carcas percentage. Result from this research showed that feed consumption, daily gain, final weight and carcas percentage are increase significantly in line with the increasing of fermented tofu by product level, but carcas percentage was not significant. Meanwhile feed convertion significantly better in feeds contain fermented tofu by product. Conclusion taken from this research are fermented tofu by product increasing feeds quality and promoting growth of broiler.